A guide to world money and capital markets - Kemp, L. J. (London ; New York : McGraw-Hill, 1981)
The book is an essential tool for reliable decision making for investment purpose. The book will build up ones knowledge and confidence in the market, and allow one to become familiar with the individual market topics rapidly.
Includes index.
nju 20/02/2020
Ref.
Keywords: Investments; Investments, Foreign; Money market; Capital market